Translation strategy of legal terms with Chinese characteristics in Civil Code of the People’s Republic of China based on Skopos theory - An, Jing; Sun, Jiahui (PloS one, 2022)
The Civil Code of the People’s Republic of China , known as the “Encyclopedia of social life”, has come into effect since January 1, 2021. It is the first law named after the “Code” and occupies a fundamental position in the China’s legal system. Therefore, translation of legal terms is vital in making target readers familiar with the China’s civil system and contributes to cultural communication and academic exchange. Previous research on translations of legal terms provides various translation principles and strategies. However, culture connotation in Chinese is usually implicit or lacks counterparts, leading to the difficulties in the equivalent translation of legal terms with Chinese characteristics. Therefore, this paper concentrates on the selection of legal term translation principles from the perspective of the Skopos theory and a Chinese translation theory named Eco-translatology, to explore the application and effect of selected principles in the translation of legal terms with Chinese characteristics. Guided by the Skopos theory and Eco-translatology, this paper collects 42 legal terms with Chinese characteristics from the The Civil Code of the People’s Republic of China and analyzes the application of 5 translation principles of accuracy, readability, traceability, conventionality, and unification. Through analysis, the legal terms are classified into newly-coined and inherited terms and rules of strategy application are therefore summarized. It is expected that this paper would provide systematic principles for the translation of legal terms with Chinese characteristics.